Configuration of earthwork equipment considering environmental impacts, cost and schedule - Kim, Byung-Soo; Kim, Yong-Woo (Journal of Civil Engineering and Management, 2015)
Along with promotion of public awareness about sustainability, the concept of sustainability has gained in- creasing attention across all industries. The construction industry is one of the largest industries, and at the same time, among the largest polluters. Thus, the concept of sustainability has become increasingly important to construction firms and many contractors have started to reduce the environmental impacts of their construction activities. As part of the effort to achieve sustainability in construction sector, the study develops a method to select earth-moving equipment, based on their environmental impacts as well as duration and cost considerations. To this end, the study initially devel- ops a model for determining construction costs and duration as well as a model for determining monetary environmental impacts on earthwork construction. The study then uses an Improved Weight Decision Method (IWDM) to determine the weight of variables in order to find the best performed equipment configuration. The authors expect that the findings of the study will contribute to the research and practice in configuring earthwork equipment, taking into account associated environmental impacts as well as time and costs.